Analysis of the Effect of Gross Regional Domestic Product (GDP) on the Poverty Level of North Sumatra - Dian Maulida Sudirman; Nadya Desmita Gultom; Wydia Malem Pasaribu (Outline Publisher, 2025)
This study aims to determine the effect of Gross Regional Domestic Product (GDP) on the Poverty Level of North Sumatra. The population in this study is the highest percentage of poor North Sumatera residents who rank 19th nationally from 2011 to 2022. The research method used in this research is quantitative descriptive and the analytical technique used is simple linear regression analysis. From the results of simple linear regression analysis to determine the effect of GRDP (X) on poverty (Y) it can be seen that the constant is positive, this means that GRDP (X) and poverty (Y) show a unidirectional influence. The results of the research t-test partially have a positive and significant effect on the amount of poverty. Thus Ho is rejected, Ha is accepted.